2016
DOI: 10.4103/0366-6999.189925
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Trabeculotomy in Newborns with Primary Congenital Glaucoma

Abstract: Background:Early surgical intervention is required for the primary congenital glaucoma (PCG). There are currently few reports on the surgical outcomes in infants with PCG. This study aimed to evaluate the efficacy and safety of trabeculotomy and the postoperative visual outcomes in Chinese newborns with PCG within 4 weeks of birth.Methods:A total of 21 eyes of 12 patients with PCG who underwent primary trabeculotomy within 4 weeks of birth were retrospectively studied. Preoperative and postoperative intraocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Visual acuity prognosis was not addressed in several studies that evaluated the surgical outcomes of congenital glaucoma (6). However, several other studies on postoperative PCG outcomes reported variable VA outcome (5,9,(14)(15)(16). A normal to near-normal VA (20/20 to 20/50) was achieved in 41%-79% of eyes, as summarized in Table VI (5,9,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 96%
“…Visual acuity prognosis was not addressed in several studies that evaluated the surgical outcomes of congenital glaucoma (6). However, several other studies on postoperative PCG outcomes reported variable VA outcome (5,9,(14)(15)(16). A normal to near-normal VA (20/20 to 20/50) was achieved in 41%-79% of eyes, as summarized in Table VI (5,9,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 96%
“…This technique has been previously described 8. In brief, a superior quadrant fornix-based flap will be created.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Trabeculotomy reduces intraocular pressure (IOP) by tearing the trabecular meshwork into the anterior chamber. Regarding complications, hyphema is more common in trabeculotomy but can resolve spontaneously and cause no additional problems 7–9…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 A clear cornea that permits good visualization of the angle structures is an essential parameter for goniotomy. 14 , 15 A cloudy and opacified cornea due to markedly elevated IOP is typically found in buphthalmos cases. Trabeculotomy is believed to be the ideal surgery in this situation, 15–17 while goniotomy can be performed with some effort; typically, the surgeon has to choose between goniotomy and trabeculotomy.…”
Section: Introductionmentioning
confidence: 99%
“…14 , 15 A cloudy and opacified cornea due to markedly elevated IOP is typically found in buphthalmos cases. Trabeculotomy is believed to be the ideal surgery in this situation, 15–17 while goniotomy can be performed with some effort; typically, the surgeon has to choose between goniotomy and trabeculotomy. 18 The selection of surgery may depend on the corneal diameter, as successful incisional angle surgery may be restricted to corneal diameters less than 14 mm.…”
Section: Introductionmentioning
confidence: 99%